Cognitive Structuring and Its Cognitive-Motivational Determinants as an Explanatory Framework of the Fear-Then-Relief Social Influence Strategy - Dolinski, Dariusz; Dolinska, Barbara; Bar-Tal, Yoram (Frontiers in Psychology, 2017)
According to the fear-then-relief technique of social influence, people who experience anxiety whose source is abruptly withdrawn usually respond positively to various requests and commands addressed to them. This effect is usually explained by the fact that fear invokes a specific program of action, and that when the source of this emotion is suddenly and unexpectedly removed, the program is no longer operative, but the person has not yet invoked a new program. This specific state of disorientation makes compliance more likely. In this paper, an alternative explanation of the fear-then-relief effect is offered. It is assumed that the rapid change of emotions is associated with feelings of uncertainty and confusion. The positive response to the request is a form of coping with uncertainty. In line with this reasoning, while individuals with a high need for closure should comply with a request after a fear–then-relief situation, low need for closure individuals who are less threatened by uncertainty should not. This assumption was confirmed in the experiment.